Legal Politics and Data Protection in Indonesia: A Case Study of the National Data Center Hacking - Gani, Najamuddin (SASI, 2024)
Introduction: This article analyzes the politics of law and data protection in Indonesia through a case study of the hacking of the National Data Center. The incident highlights significant vulnerabilities within the national data protection framework and the legal implications arising from such breaches, emphasizing the urgent need for robust legal measures to safeguard sensitive information.Purposes of the Research: The purpose of this article is to thoroughly evaluate legal policies related to data protection in Indonesia, examining the challenges and opportunities for improvement. By focusing on the hacking incident of the National Data Center, the study aims to provide insights into potential policy enhancements to better protect data in an increasingly digital world.Methods of the Research: This research employs normative research methods with a comprehensive case study approach. Data is obtained through detailed analysis of legal documents, pertinent regulations, and relevant literature. This methodology aims to offer an in-depth understanding of the current state of data protection policies in Indonesia and identify areas requiring legislative and regulatory improvements.Results of the Research: The findings reveal that current data protection policies in Indonesia are insufficient to counter advanced hacking threats. This study offers recommendations for strengthening regulatory frameworks and implementing tighter supervision to enhance national data security. It introduces a new perspective on the dynamics of data protection law politics in Indonesia, contributing to the broader discourse on data security.